Electrostatic self-assembled Iridium(III) nano-photosensitizer for selectively disintegrated and mitochondria targeted photodynamic therapy. (April 2020) - Deng, Yong; Pan, Shunjie; Zheng, Jiajun; Hong, Yale; Liu, Jie; Chang, Haizhou; Miao, Yuqing; Sun, Yun; Li, Yuhao
Abstract: Photodynamic therapy (PDT) is one of effective cancer therapy methods. It is important to develop a PDT reagent with tumor-targeted ability, high phototoxicity and low dark toxicity. In this study, an iridium(III) complex (Irpy) can electrostatically self-assemble with hyaluronic acid (HA) to form nanostructured Irpy-HA, which exhibited stable spheroid structure and outstanding ability of singlet oxygen ( 1 O2 ) generation. The photophysical property of Irpy has been well studied, which qualified green light absorption ability and could emit red phosphorescence. The nanostructure and stability of self-assembled Irpy-HA have been well investigated, which can keep its nanostructure at least 30 days. More importantly, Irpy-HA can target to a CD44 receptor in cancer cell membrane for enhancing internalization and selective disintegration. Then, Irpy can accumulate in mitochondria and generate 1 O2 to realize PDT-induced cell apoptosis by green light irradiation. The Irpy-HA could be used as a nanophotosensitizer for effective photodynamic therapy. Graphical abstract: Image 1 Highlights: An Ir(III) complex Irpy can electrostatically self-assemble with hyaluronic acid (HA) to form nano-structured Irpy-HA. Irpy-HA can target to a CD44 receptor for enhancing tumor cell internalization. Irpy-HA can accumulate in mitochondria to generate 1 O2 for photodynamic therapy.